TRANSNATIONAL ASPECTS OF THE POETICS OF MARJANA GAPONENKO’S NOVEL “WHO IS MARTHA?” - Oleksii I. Ankhym.; Natalia I. Astrakhan (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2023)
The article is devoted to researching the creativity of the modern German-speaking writer of Ukrainian origin Marjana Gaponenko. The object of the research is the novel “Who is Martha?” (2012), for which the author received a prestigious literary award in 2013 – the Adelbert von Chamisso Prize. The aim of the research is to carry out a terminological distinction of concepts that since the 90s of the 20th century have been increasingly used to denote literature of migrant authors, as well as to identify and analyze those characteristic features of poetics by which Marjana Gaponenko’s novel can be determined as transnational. The task of the study is to determine the peculiarities of transnational literature and carry out a three-level (biographical-referential, thematic-content and text-structural) decoding of the novel “Who is Martha?” with a focus on narrative techniques of transnational writing. Biographical, historicalliterary, philological, intertextual, intermedial and hermeneutic methods of research were involved in order to achieve the stated aim and solve the tasks. Conclusion. In the postmodern era, traditional concepts of national literature, culture, and identity are being more and more questioned and become conditional. Transnational movements and processes of hybridization level national, ethnic, and cultural boundaries, and migration itself becomes an integral part of existence and often an impetus for literary creativity. Despite the fact that literary texts against the background of the migration experience were written earlier as well, it was in the 1990s that this phenomenon acquired a new expression and sound. Transnational literature with its immanent explicit and implicit reflection on transculturality, separating from the homogenizing essentialist concepts of identity and culture, as well as national and cultural affiliations, overcomes the contradictions between national and minority literature, between “own” and “foreign” and offers a productive approach to texts that were previously assigned to classification categories focused primarily on authors. The cognitive value of this concept lies in its special validity when studying the literary works by transmigrant authors as representatives of a new generation that freely chooses its place of residence and the language of literary expression. The conducted three-level decoding of Marjana Gaponenko’s novel substantiates the thesis that it belongs to transnational literature, the characteristic features of which are manifested at all levels of the artistic organization of the work. At the biographical-referential level, Marjana Gaponenko, taking into account her life and creative path, can be called a transnational author who belongs to postmodern transmigrants. This definition makes it possible to analyze the peculiarities of poetics in the novel “Who is Martha?”, which artistically implements the autobiographical experience of migration at the thematic-content level, but goes beyond these limits. While other migrant authors mostly deal with their own migration, artistic experience of identity crisis, loss and alienation, Marjana Gaponenko explores global essential topics, considering them in a broad cultural, historical and philosophical context. At the text-structural level, characteristic manifestations of transnationality are the spatial structure of the text, the use of dynamic heroes with hybrid identities (Marjana Gaponenko’s characters are postmodern cosmopolitans with inherent linguistic and cultural hybridity, who are searching for and eventually find essential truths beyond various boundaries), the presence of elements of analepsis and prolepsis, involvement of double characters, the inclusion of multilingualism and dialects, the use of stereotypes, tendency to blur genres, etc. Marjana Gaponenko’s novel with its cultural, linguistic and literary hybridity, as well as peculiar manifestations of intertextuality and intermediality, ultimately not only expands the space of reader’s reception and literary knowledge, but also ensures the development of a productive transcultural and transnational dialogue.